1972
DOI: 10.1111/j.1365-2362.1972.tb00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Further Aspects on the Characterization of High and Very Low Density Lipoproteins in Patients with Liver Disease

Abstract: Various liver disorders are often associated with decreased concentrations of serum a-and pre-b-lipoproteins. The decreased concentrations of high density lipoproteins (HDL) is primarily due to an impaired lipid binding capacity of apolipoprotein A (apo -4), the major protein moiety of HDL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

1976
1976
1987
1987

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(14 citation statements)
references
References 23 publications
3
10
0
1
Order By: Relevance
“…4), a mechanism which is important for plasma lipoprotein metabolism. The hypertriglyceridaemia of cholestasis may be caused by such a mechanism, a view which is supported by the observation that these apolipoproteins are either absent or drastically reduced in VLDL particles obtained from patients with cholestasis (25,27).…”
Section: Cholestasis and Hypercholesterolaemiamentioning
confidence: 48%
See 4 more Smart Citations
“…4), a mechanism which is important for plasma lipoprotein metabolism. The hypertriglyceridaemia of cholestasis may be caused by such a mechanism, a view which is supported by the observation that these apolipoproteins are either absent or drastically reduced in VLDL particles obtained from patients with cholestasis (25,27).…”
Section: Cholestasis and Hypercholesterolaemiamentioning
confidence: 48%
“…These unusual particles are heterogeneous in size, ranging from 30 nm to 80 nm, and are thus much larger than normal LDL (20 -25 nm). Dietary studies have indicated that these particles are remnants derived from a disturbed catabolism of chylomicrons (25). Their accumulation may be caused by reduced plasma lipolytic activity and/or by a disturbed hepatic uptake due to an Inhibition of the apolipoprotein E receptor.…”
Section: Hypertriglyceridaemiamentioning
confidence: 99%
See 3 more Smart Citations